Magnetic field source for dark mode spectroscopy - Stanek, Frantisek; Pistora, Jaromir; Lesnak, Michal (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The paper is focused on the study of two-dimensional magnetic field distribution used for the analysis of the samples containing magnetically active films by means of dark mode spectroscopy (DMS). The design of proposed electromagnet for in-plane magneto-optic configuration and the magnetic field model computation are presented together with the results obtained from magnetic field distribution measurement.
Optica Applicata, Vol. 40, 2010, nr 3, s. 719-726
Keywords: optyka; dark mode spectroscopy; magnetic field